Reading modern drama - Ackerman, Alan L. (Alan Louis) (University of Toronto Press, 2012)
Taken together, these essays enter into an ongoing, fruitful debate about the terms 'modern' and 'drama' and build a much-needed bridge between literary studies and performance studies.